FORMATION OF A METHODOLOGICAL APPROACH TO CHOOSE AN HR MANAGEMENT STRATEGY TO ENSURE THE FINANCIAL SECURITY OF AN ENTERPRISE - Oksana Verbova (Фінансово-кредитна діяльність: проблеми теорії та практики)
In today's conditions, personnel security has reached a completely different level. The problem of human resource management at an enterprise is increasingly becoming a significant factor in determining the level of not only economic security but also has a direct impact on the financial condition and protection of financial interests. In such conditions, HR management is a key element of any strategy for the safe development of an enterprise. At the same time, the strategy for ensuring financial security also depends on the choice of the strategy itself. Therefore, we consider it necessary to form an appropriate methodological approach that will allow, based on the results obtained, to choose the right HR management strategy to ensure the financial security of the enterprise. For this purpose, the key object is not only the parameters for choosing an HR management strategy at the enterprise but also financial security, in particular. We have formed a clear sequence of selection and justification of the optimal HR management strategy in order to ensure the financial security of the enterprise. At the same time, as a result of the analysis of the most well-known methods for solving multi-criteria problems, we have chosen the Zadeh fuzzy set theory method, which will form the basis of the proposed methodological approach. Key term sets for determining degrees of membership are identified. The results of fuzzy sets made it possible to construct graphs of utility functions. This, in turn, allowed to form a fuzzy knowledge base for choosing the optimal HR management strategy to ensure the financial security of the enterprise. Detailed justification of all components of the formed methodological approach allowed us to state the possibility of its practical application in the activities of modern Ukrainian enterprises in the future.